SILICON PLASTINATION OF BRACHIAL AND LUMBOSACRAL PLEXUSES AND CAUDA EQUINA IN GOAT; EDUCATIONAL NEUROANATOMICAL STUDIES - Seleem; Basset Aly; A.E; A.A. Mohamed Sh. Kh (Basrah Journal of Veterinary Research)
Plastination of nervous tissue has become a very important tool in teaching neuroanatomy. Also, plastinated nervous specimens can be used to study the anatomical relations in clinics right before surgical operations. The aim of using plastinated models is to increase knowledge, understanding as well as imagination of students about the complex anatomical parts of the central nervous system. The plastinated anatomical teaching model of Medulla spinalis, Plexus brachialis, Plexus lumbosacralis and Cauda equina of goat displays a clear morphology that corresponds qualitatively to the actual cadaver specimens. Apparently healthy four goats (ten months age) from native breed were used. Goats were subjected to silicone S10 plastination technique. Prior to plastination, the goat was prepared by injected via I/V by Xylazine Hcl (0.01mg/kg), cutting Arteria carotis communis for complete bleeding, and injected via the latter artery with 10% formalized solution then immersed in the same solution for at least four weeks. Medulla spinalis and attached peripheral nerves, Plexus brachialis, Plexus lumbosacral and Cauda equina were dissected. The purpose of this paper is to enhance the teaching of the neuroanatomy of the goat in our department. Particularly, Medulla spinalis, Nervi cervicales, Plexus brachialis, Nervi thoracici, Plexus lumbosacralis and Cauda equina were selected as learning models in special unit in the department and provide a plastinated model to study the anatomy of this system. Understanding of the astudents but also for veterinary doctors while undertaking surgery on that plexuses and nerves.anatomy of the nervous system is important not only for veterinary